Peranan Geografi Sebagai Poros Pembangunan di Era Revolusi Industri 4.0 dan Society 5.0 - Irawati, Pipit; Isrotun, Umi; Inajati, Ani Satul (CV. Supernova Office Stationary and Printing, 2023)
In the era of the Industrial Revolution 4.0, the development of digital technology and the internet has changed the way people work, interact and access information. Geography plays an important role in managing this change, including in the development of digital infrastructure, spatial data analysis, and supply chain management. Geography also plays a role in supporting integration between physical and digital sectors, such as location-based logistics and smart city center development. Society 5.0, which emphasizes combining digital technology with a human-centred society, requires a deep understanding of the interrelationships between humans, the environment and technology. Geography can help map and analyze social, cultural and economic dynamics in society 5.0. Through a geospatial approach, geography can also integrate data and knowledge across sectors to facilitate better decision-making in addressing complex challenges, such as climate change, social inequality and natural resource management. In this era, geography also plays a role in developing sustainable development concepts and strategies. By considering geographical aspects such as location, environmental conditions, and resource availability, geography can help plan environmentally friendly infrastructure development, increase resilience to natural disasters, and optimize the efficient use of resources. In conclusion, geography has an important role as the axis of development in the era of the Industrial Revolution 4.0 and Society 5.0. The discipline of geography starting from elementary school to the highest level is needed to assist in the management of technological and societal changes, socio-economic analysis, and the development of sustainable development strategies. In facing future challenges, the application of geographic knowledge is the key to achieving sustainable and inclusive development.